2019
DOI: 10.1039/c9tb01480b
|View full text |Cite
|
Sign up to set email alerts
|

Smart supramolecular gels of enolizable amphiphilic glycosylfuran

Abstract: In this report, bio-based amphiphilic glycosylfurans were synthesized using a biocatalyst. For the first time, we are reporting on hydrogelation via in situ molecular tuning of amphiphilic glycosylfurans followed by a self-sorting mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…On the other hand, gels are interesting soft materials owing to their functional properties, leading to potential applications (Yao et al, 2017). Using gels as drug carriers has attracted tremendous attention for their numerous advantages in medical treatments, including prolonged drug release time, reduced side effects of drugs, and maintained effective plasma concentration (Nishimura et al, 2019;Teng et al, 2019;Thamizhanban et al, 2019). For example, Prof. Yao and co-workers prepared a soft gel based on pillar[5]arene by using a carbazone reaction and found that dyes such as TPP or TPPE can be incorporated into this gel and then released in a sustained way in water due to solvent exchange (Yao et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, gels are interesting soft materials owing to their functional properties, leading to potential applications (Yao et al, 2017). Using gels as drug carriers has attracted tremendous attention for their numerous advantages in medical treatments, including prolonged drug release time, reduced side effects of drugs, and maintained effective plasma concentration (Nishimura et al, 2019;Teng et al, 2019;Thamizhanban et al, 2019). For example, Prof. Yao and co-workers prepared a soft gel based on pillar[5]arene by using a carbazone reaction and found that dyes such as TPP or TPPE can be incorporated into this gel and then released in a sustained way in water due to solvent exchange (Yao et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Both functionalized furans hold promise as precursors for platform chemicals, value-added chemicals, pharmaceutical intermediates, and materials. To date, these functionalized furans have been used to access a variety of anticancer agents, 9 antimicrobials, 10 antifungals, 10 glyco-mimetics, 11 biological probes, 12 hydrogels, 13 and fuel precursor molecules. 14 Despite this promise, scalability issues have limited the reaction's broader utility.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For example, using 2-nitroterephthalic acid instead of terephthalic acid in the synthesis of UiO-66 has led to a more Lewis acidic zirconium node for Lewis acid catalyzed reactions. 45 The Garcia Gonzalez product is of increased interest, due to acting as a precursor in biologically active molecules, 9−12 materials, 13 various synthetic motifs, and fuel applications. 14 Due to this understudied reaction being catalyzed primarily by homogeneous catalysts, we have focused on developing a wellcharacterized, truly heterogeneous catalyst in the form of a zirconium MOF.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In recent years, the design and study of sugar based gelators have attracted much attention. They have been explored for applications in several research fields ranging from drug delivery [ 5 , 6 , 7 , 8 ], to environmental applications [ 9 , 10 , 11 , 12 , 13 , 14 ], enzyme immobilization, ion sensing [ 15 , 16 , 17 ], and supramolecular gel catalysts [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%